Experimental and Numerical Investigation on Hydraulic Fracture Propagation Law of Composite Rock Materials considering the Disturbing Stress Effect - Xin Zhang; Yuqi Zhang; Tao Zhang (Geofluids)
The stress disturbance effect will significantly affect the propagation path of hydraulic fractures in the composite rock reservoir. To reveal the influence mechanism of stress disturbance effect on the hydraulic fracture propagation, several groups of laboratory tests and simulation tests were carried out. The test results showed that the hydraulic fracture tip formed a disturbing stress field because of the pore water pressure. Before the hydraulic fracture was extended to the bedding plane, the bedding plane had been damaged under stress disturbance, and the disturbed fracture zone was formed. The propagation mode of hydraulic fracture at the bedding plane was highly sensitive to the formation of the disturbed fracture zone. The sensitivity is mainly reflected from two aspects. (1) Under the action of the hydraulic fracture tip disturbance stress, many microfractures are generated and penetrated into the disturbance fracture zone on the bedding plane. This behavior is accompanied by energy dissipation causing the bedding plane material to be significantly softened, and the energy required for hydraulic fracture propagation is reduced dramatically. (2) The formation of the disturbed fracture zone improves the degree of fragmentation of the bedding plane, and the permeability of the local area increases significantly, forming the dominant circulation path. The higher the development of the disturbed fracture zone, the greater the hydraulic fracture propagation tendency along the bedding plane. According to the formation characteristics of the bedding plane disturbed fracture zone, the author proposed a nonlinear fracture model of the bedding plane disturbed fracture zone and established the hydraulic fracture propagation path criterion. This paper further analyzed the influencing factors of the disturbed fracture zone’s formation conditions and found that the bedding plane’s cementation strength was the main factor affecting the development degree of the disturbed fracture zone.